2021
DOI: 10.1111/1759-7714.13998
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ferroptosis‐related genes in patients with lung adenocarcinoma

Abstract: Background The prevalence of lung adenocarcinomas (LUADs) has dramatically increased in recent decades. Ferroptosis is a process of iron‐dependent regulatory cell death. It is still unclear whether the expression of ferroptosis‐related genes (FRGs) is involved in the pathogenesis and survival of patients with LUAD. Methods We retrieved LUAD data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) databases and used LASSO Cox regression analysis to select the gene signature suitable for modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…Besides, results from both difference in APC co-stimulation and co-inhibition appears contradictory in the immune microenvironment. However, we found the results are somewhat similar to the researches about ferroptosis-related signature in other cancers (6,(89)(90)(91). Though the mechanisms illustrating tumor susceptibility to ferroptosis have been an intense area of research in past decades, the complex relationship between tumor immunity and ferroptosis remains elusive.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, results from both difference in APC co-stimulation and co-inhibition appears contradictory in the immune microenvironment. However, we found the results are somewhat similar to the researches about ferroptosis-related signature in other cancers (6,(89)(90)(91). Though the mechanisms illustrating tumor susceptibility to ferroptosis have been an intense area of research in past decades, the complex relationship between tumor immunity and ferroptosis remains elusive.…”
Section: Discussionsupporting
confidence: 84%
“…FANCD2, a nuclear protein that responds to DNA damage repair, negatively regulated ferroptosis of bone marrow injury in cancer treatment and could be a potential target of anticancer therapies ( Song et al, 2016 ). In addition, a 10 ferroptosis-related genes signature and a ferroptosis-related gene signature with five genes were constructed to predict the prognosis of patients with LUAD ( Wang S. et al, 2021 ; Zhu et al, 2021 ). In general, ferroptosis-related genes play important roles in the progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Duan et al 18 constructed a prognostic signature based on ARGs, which served as a novel biomarker in LUAD. Meanwhile, Zhu et al 21 identi ed a ferroptosis-related gene signature and explored the immune cells in ltration. In this study, several ARlncRNAs included in the modeling process have been already reported in various malignant tumors, such as CARD8-AS1 22 23 , AC060780.1 24 , AC123595.1 25 26 , UGDH-AS1 27 , LINC00996 28 , LINC00861 29 30 31 , AL606489.1 17 , HLA-DQB1-AS1 32 , LINC00654 33 LINC00847 34 35 .…”
Section: Discussionmentioning
confidence: 99%